Hubungan Efikasi Diri dan Stres Kerja Perawat Dengan Pengetahuan Penatalaksanaan RJP Di IGD RSUD Brigjend H. Hasan Basry Kandangan - M. Fadillah; Julianto, Julianto; Daud, Izma; Khalilati, Noor (LPPM Universitas Sari Mulia, 2023)
Background: Scabies is a skin disease that is often found in Islamic boarding schools. Factors that influence the incidence of scabies are poor personal hygiene and unqualified occupancy density, thus accelerating the transmission and transmission of scabies. Objective: To determine the relationship between personal hygiene and occupancy density with the incidence of scabies skin disease. Method: This study uses a quantitative correlational research design with a cross-sectional approach. The data collection instruments used were personal hygiene questionnaires, observation sheets of occupancy density, and observation sheets of the incidence of scabies skin disease. Result: Based on the results of the Chi-Square Test show that the value of p = 0.000 <α = 0.05 the value is statistically meaningful (p < 0.05), meaning that it shows that there is a relationship between personal hygiene and occupancy density with the incidence of scabies skin disease in Islamic boarding schools. Conclusion: There is a significant relationship between personal hygiene and occupancy density with the incidence of scabies skin disease. Keywords: Personal Hygiene, Occupancy Density, Scabies Skin Disease.